Management And Technology In Islamic Education: Integrative Strategies For The Digital Era - Sadiyah, Arini; Firdausiah, Nuri; Alfatani, Ifan Ali (EDUSHOPIA : Journal of Progressive Pedagogy, 2025)
ABSTRACT The development of information and communication technology has significantly influenced the education sector, including Islamic educational institutions. In the digital era, Islamic education is challenged to adapt to technological advancements while upholding its core religious and ethical values. This study aims to explore integrative strategies that combine educational management and technology within Islamic institutions. Using a qualitative descriptive approach through literature review, the study examines various scholarly sources related to Islamic educational management, digital transformation, and educational technology. The findings indicate that effective integration of management and technology can enhance administrative efficiency, improve the quality of learning, and expand access to Islamic knowledge. However, the integration process requires strategic planning, adequate digital literacy among educators, and policies aligned with Islamic values. The study concludes that successful digital transformation in Islamic education depends on visionary leadership, institutional readiness, and the development of a tech-aware yet value-based educational culture. Recommendations include developing digital roadmaps for Islamic schools, providing continuous professional development, and promoting further field-based research on technology implementation in Islamic educational settings.